MEASUREMENT OF QUALITY PARAMETERS OF SIMPLICIA AND EKSTRACT OF KECOMBRANG STEM (Etlingera elatior) - Adini, Syilvi; Shobah, Afifah Nur; Chandra, Pra Panca Bayu (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Kecombrang (Etlingera elatior) is a type of plant known to the Indonesian people as a medicinal plant for a long time. Kecombrang stem is empirically used to treat coughs, reduce fever, act as an antiseptic, treat diarrhoea and stomach pain. Kecombrang stem has the potential to be used as a raw material for herbal medicines. Plants used as raw materials for herbal medicines must meet quality requirements in accordance with the requirements of both specific and non-specific parameters. This study aimed to determine the quality of the simplicia and 96% ethanol extract of kecombrang stem. Simplicia and 96% ethanol extract were tested for specific parameters, including organoleptic, microscopic, and phytochemical screening. Non-specific parameter testing includes the measurement of moisture content, residual solvents, and microbial contamination. Tests of specific parameters on organoleptic kecombrang stem simplicia are light brown, aromatic odor, and tasteless. Microscopically, kecombrang stem simplicia was identified with fragments consisting of transport bundles, ladder-type transport bundles, fibers, and parenchyma with secretory cells. Phytochemical screening of kecombrang stem simplicia revealed the presence of alkaloids, phenolics, flavonoids, steroids, tannins, and saponins. The results of non-specific parameter testing on 96% ethanol extract of kecombrang stem showed 1.09% moisture content, 0.48% solvent residue, 0 CFU/g bacterial contamination, and yeast/mould. Kecombrang stem is a raw material for herbal medicine that meets the quality requirements of specific and non-specific parameters. Keywords: Etlingera elatior, Non-specific parameters, Simplicia quality, Specific parameters.